The effectiveness of the elements that frame cancer charity TV advertisements in Egypt: A case study on 57357 CCHF - Kasseb, Yasmine (AUC Knowledge Fountain, 2019)
This study analyzed the elements that frame the cancer charity TV advertisements in Egypt and examined the reasons behind its effectiveness from the creator’s point of view. 57357 CCHF was taken as a case study, as it is considered to be one of the well-branded charity organizations that uses TV advertisements effectively. A mixed-method approach was conducted, and it included a content analysis and a focus group. The content analysis covered three years of Ramadan TV advertising campaigns for 57357 CCHF to examine the major elements that were used in its TV advertisements like the type of the appeals, message frame, image valence, message strategy, executional framework, patient depiction, the type of spokesperson endorsement, the type of donation reframing, and of the call for action. Then a focus group was conducted with the marketing and the media team of 57357 to understand the reasons behind their selection of these elements. The results of the content analysis showed that gain framing is the main message frame used by 57357 CCHF, the affective strategy is the strategy most implemented, the main appeal used is the positive appeal, and the positive image valance and the mixed images are the most executed. The results also revealed that the testimonial is the framework most used in the TV advertisements for 57357 CCHF, the donation reframing wasn’t used significantly, the patients were depicted in most of the advertisements, the most applied call for action is donation, and the most used type of the spokesperson endorsers are religious icons (Sheikhs) and celebrities. The results of the focus group revealed that these elements are the most used elements because of their effective impact on the target audiences, which is reflected on the donations. The participants also stated that negative types of these elements can be used to reflect the reality of the patients, but they should be followed by positive elements to avoid any kind of psychological stress on the target audiences and the patients. The patients can be depicted in the advertisements but there are rules for their depiction that protect their rights and dignity. Additionally, the results indicate that the congruent implementation of the advertising appeal, message frame, and image valence wasn’t significant in the TV advertisements for 57357 CCHF; the participants in the focus group stated that the congruent implementation of these elements attracts the target audiences, but it will not reflect the reality, which is their main goal. Finally, the conclusion of the study showed that the positive elements that frame the cancer charity TV advertisements attract the target audiences and motivate them to perform the call for action, but the use of positive elements only will not reflect the reality of the patients. Negative elements can be used but they should be supported with positive elements to avert their negative impact on the audiences, and to evade the ignorance of the target audiences to the advertisements. The gain framing, positive image valence, positive appeals, affective strategy, and the testimonial framework are the most used elements in TV advertisements for 57357 CCHF. The spokesperson endorsement increases the credibility and the attractiveness level of the advertisements, and the patients’ depiction increases its reliability.